Effect of altered production and storage of dopamine on development and behavior in C. elegans - Lee, Irene; Knickerbocker, Ava C.; Depew, Charlotte R.; Martin, Elizabeth L.; Dicent, Jocelyn; Miller, Gary W.; Bucher, Meghan L. (Frontiers in Toxicology, 2024)
IntroductionThe nematode, Caenorhabditis elegans (C. elegans), is an advantageous model for studying developmental toxicology due to its well-defined developmental stages and homology to humans. It has been established that across species, dopaminergic neurons are highly vulnerable to neurotoxicant exposure, resulting in developmental neuronal dysfunction and age-induced degeneration. C. elegans, with genetic perturbations in dopamine system proteins, can provide insight into the mechanisms of dopaminergic neurotoxicants. In this study, we present a comprehensive analysis on the effect of gene mutations in dopamine-related proteins on body size, development, and behavior in C. elegans.MethodsWe studied C. elegans that lack the ability to sequester dopamine (OK411) and that overproduce dopamine (UA57) and a novel strain (MBIA) generated by the genetic crossing of OK411 and UA57, which both lack the ability to sequester dopamine into vesicles and, additionally, endogenously overproduce dopamine. The MBIA strain was generated to address the hypothesis that an endogenous increase in the production of dopamine can rescue deficits caused by a lack of vesicular dopamine sequestration. These strains were analyzed for body size, developmental stage, reproduction, egg laying, motor behaviors, and neuronal health utilizing multiple methods.ResultsOur results further implicate proper dopamine synthesis and sequestration in the regulation of C. elegans body size, development through larval stages into gravid adulthood, and motor functioning. Furthermore, our analyses demonstrate that body size in terms of length is distinct from the developmental stage as fully developed gravid adult C. elegans with disruptions in the dopamine system have decreased body lengths. Thus, body size should not be used as a proxy for the developmental stage when designing experiments.DiscussionOur results provide additional evidence that the dopamine system impacts the development, growth, and reproduction in C. elegans. Furthermore, our data suggest that endogenously increasing the production of dopamine mitigates deficits in C. elegans lacking the ability to package dopamine into synaptic vesicles. The novel strain, MBIA, and novel analyses of development and reproduction presented here can be utilized in developmental neurotoxicity experiments.